Comorbidities and the decision to undergo or forego destination therapy left ventricular assist device implantation: An analysis from the Trial of a Shared Decision Support Intervention for Patients and their Caregivers Offered Destination Therapy for End-Stage Heart Failure (DECIDE-LVAD) study - Warraich, Haider J.; Allen, Larry A.; Blue, Laura J.; Chaussee, Erin L.; Thompson, Jocelyn S.; McIlvennan, Colleen K.; Flint, Kelsey M.; Matlock, Daniel D.; Patel, Chetan B. (The American heart journal, 2019)
Patients considering destination therapy left ventricular assist devices (DT LVAD) often have high comorbid burden but the association between these comorbidities and post-decision outcomes is unknown. We included subjects in DECIDE-LVAD (NCT02344576), a stepped-wedge multicenter trial of patients considering LVADs, recording comorbidities per INTERMACS protocol. We compared decisional conflict, regret, perceived stress, quality of life (EQ-VAS), depression (PHQ-2), struggle with- and acceptance of illness by comorbid burden and amongst the most common comorbidities. Of 239 patients, LVAD recipients (n = 164) and non-recipients (n = 75) had a similar proportion with ≥1 comorbidity (70% v. 80%, P = .09). Patients with comorbidities were younger regardless of LVAD implantation status. After adjusting for age, overall and amongst LVAD recipients, patients with ≥1 comorbidity had higher mean decision conflict at baseline (23.2 ± 1.5 vs. 17.4 ± 2.2), and at 6 months, higher stress (13.0 ± 0.6 vs. 10.4 ± 1.0) and struggle with illness (13.3 ± 0.4 vs. 11.1 ± 0.6) than those without comorbidities (P < .05). No difference was noted in decision regret, PHQ-2, EQ-VAS, acceptance of illness and survival overall and amongst LVAD recipients. Of the three most common comorbidities, while patients with pulmonary hypertension had worse decision regret, depression, stress and acceptance of illness at 6-month follow-up than those who did not have pulmonary hypertension, no difference was noted in patients with chronic renal disease or high body mass index. Patients considering LVAD implantation with comorbidities experience increased decision conflict, stress and struggle with illness. These findings provide insights in the role comorbidities play in patient decision-making and decisional outcomes.